1999
DOI: 10.1143/jjap.38.6817
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dielectric Properties in SrTiO3/BaTiO3 Strained Superlattice Structures Prepared by Atomic-Layer Metalorganic Chemical Vapor Deposition

Abstract: We describe the investigation of epitaxial SrTiO 3 /BaTiO 3 strained superlattice films prepared by an atomic-layer metalorganic chemical vapor deposition (ALMOCVD) method. Transmission electron microscopy (TEM) observation shows that the multilayered structure is globally uniform and that the interfaces formed between the different layers are of low roughness. Xray diffraction (XRD) analysis reveals a series of satellite peaks on both sides of the zero-order peak, a characteristic feature of the superlattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The position of the main peak in the ͑002͒ CTR spectra is determined by the average c-axis length of the superlattice. 12 The main peak position of superlattice with stacking periodicity below 16 nm shifts toward a low L index comparing to the weighted mean of the c-axis length of bulk BTO and LNO films (Lϭ1.968) indicating the elongation of BTO lattice along ͓00L͔ by the heteroepitaxial strain in superlattice, although the c-axis parameter of the individual sublayers cannot be obtained directly from the CTR spectra due to the coherent interference from the sublayer structure. 17 Since satellite peaks appear in the vicinity of the main peak at an angle interval corresponding to the superlattice period, the period of superlattice (t BTO ϩt LNO ) can be calculated from the angle intervals between satellite peaks following the formula 18 below,…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The position of the main peak in the ͑002͒ CTR spectra is determined by the average c-axis length of the superlattice. 12 The main peak position of superlattice with stacking periodicity below 16 nm shifts toward a low L index comparing to the weighted mean of the c-axis length of bulk BTO and LNO films (Lϭ1.968) indicating the elongation of BTO lattice along ͓00L͔ by the heteroepitaxial strain in superlattice, although the c-axis parameter of the individual sublayers cannot be obtained directly from the CTR spectra due to the coherent interference from the sublayer structure. 17 Since satellite peaks appear in the vicinity of the main peak at an angle interval corresponding to the superlattice period, the period of superlattice (t BTO ϩt LNO ) can be calculated from the angle intervals between satellite peaks following the formula 18 below,…”
Section: Resultsmentioning
confidence: 93%
“…[7][8][9] It has been shown that the superlattice of BaTiO 3 /SrTiO 3 ͑BTO/STO͒ has a significant dielectric enhancement. [10][11][12] For the superlattice materials, composite effect from individual compounds and their interface usually dominates the material property. However, in BTO/STO superlattice system, the role of interface was rarely characterized and the contribution of individual compounds on the dielectric enhancement is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the dielectric constant increases with decreasing period of the superlattices. This is because the polarization is effected by the stress due to the mismatching of different layers in the superlattice [33]. This suggests also the dielectric constant can be controlled artificially by fixing the period of the superlattice with RF sputtering.…”
Section: Article In Pressmentioning
confidence: 99%
“…There are several reports on the ALD of STO, 16,17 BaTiO 3 ͑BTO͒, 16 and nanolaminated STO/BTO 18,19 films. Among them, the nanolaminated STO/BTO ALD process is performed at very high temperature ͑Ͼ600°C͒, which thermally decomposes the metallorganic precursors, bis͑2,2,6,6-tetramethyl-3,5-heptanedionato͒Sr ͓Sr͑C 11 H 19 O 2 ͒ 2 , Sr͑thd͒ 2 ͔ and Ti-tetraisopropoxide ͓Ti͑Oi-C 3 H 7 ͒ 4 , TTIP͔.…”
mentioning
confidence: 99%